The Effect of Budgetary Slack, Honesty Concern, and Desire to Honesty Managerial Budget Reporting - Maya Arisandy (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2022)
This study examined the effect of budgetary slack, honesty concern, and desire to honesty managerial budget reporting. The object of this research is a manager in charge of purchasing management, finance, production, information systems and information quality, which is in the province of Banten, especially in Cilegon city. The city serve as a sample with 125 questionnaires distributed, but the questionnaire which can be processed as many as 51 questionnaires. Questions questionnaire measured with a scale of 1-5. Data were analyzed by using through SmartPLS (Partial Least Square) 1:10 version. The results of this study expressed that hypotesis from Budgetary Slack, Honesty Concern, and Desire is positive effect and significant to Honesty Managerial Reporting.